COST INSPECTION IN THE UNITED STATES NAVY. - Miller, Hermann C. (The Accounting Review, 1942)
Abstract The article discusses various aspects of cost inspection in the U.S. Navy. The writer has made a number of appointments of college graduates who have had training in accounting, but have had limited or almost no experience. These have, of course, been in the lower grades under civil-service classifications. The results produced by such appointees have been extremely gratifying. In the opinion of the writer, there is neither a basis nor justification for any adverse criticism or reservation concerning the adequacy of the training, the capacity, the devotion to duty, the loyalty, or the general adaptability of these appointees. It is believed that many employers of college graduates who insist upon the "top ten or fifteen per cent" of a senior class are overlooking many fine opportunities for obtaining capable, loyal, and efficient workers. It must not be overlooked, however, that the excellent results observed in the experiences mentioned above may be attributed in part to a capable and trained technical principal accountant and accountant, thus affording excellent supervision and direction of the less experienced personnel.